WHO/INRUD Drug Prescribing Indicators in the Emergency Ward of a Teaching Hospital, South East of Iran - Mandana Moradi; Alireza Rafighdous; Soudabeh Hamedi-Shahraki (Research Center for Rational Use of Drugs (RCRUD), 2024)
Background: Rational drug use is an important issue in all healthcare settings. Core drug use indicators have been developed by World Health Organization/ International Network for Rational Use of Drugs (WHO/INRUD). The prescribing indicators measure healthcare providers' performance in five key areas of drug usage. The aim of this study was to evaluate WHO/INRUD indicators of prescribing in emergency ward of a teaching hospital. Methods: This descriptive cross-sectional study was carried out in Emergency Ward of teaching hospital from March 2022 - March 2023. A standard prescribing indicators form was utilized to collect the required data using WHO drug prescribing indicators. Besides the rate of intravenous fluids and narcotic analgesics administration was evaluated. Index of rational drug prescribing (IRDP) was also calculated for each month and the mean of 12 IRDPs represent the emergency ward IRDP. Descriptive statistics were used for analysis. Results: Antibiotics were prescribed in 34% of studied prescriptions and ceftriaxone was the most widely used antibiotic (33.8%). Index of rational drug prescribing (IRDP) was 0.73 for polypharmacy, 0.93 for generic name prescribing, 0.88 for antibiotic prescribing, 0.1 for injectable drug use and 1 for formulary-based drug prescription. Total IRDP for the emergency ward was 3.64 (from optimal value of 5). IV fluids and narcotics were prescribed in 61.1% and 8.3% of studied prescription respectively. Conclusion: We concluded that although our overall IRDP value is below the WHO standard but it is about other neighbor countries. Our condition regarding IV drug administration showed a huge difference with WHO standards. It shows we need more input and regulations in this regard.